2020
DOI: 10.3390/jcm9061796
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Gut Microbiome and Suppression of Histone Deacetylases by Resveratrol Are Associated with Attenuation of Colonic Inflammation and Protection Against Colorectal Cancer

Abstract: Inflammatory bowel disease (IBD) is known to significantly increase the risk for development of colorectal cancer (CRC), suggesting inflammation and cancer development are closely intertwined. Thus, agents that suppress inflammation may prevent the onset of cancer. In the current study, we used resveratrol, an anti-inflammatory stilbenoid, to study the role of microbiota in preventing inflammation-driven CRC. Resveratrol treatment in the azoxymethane (AOM) and dextran sodium sulphate (DSS) CRC murine model cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 105 publications
(120 reference statements)
1
50
0
Order By: Relevance
“…Moreover, several lines of evidence have shown that the influence of T-lymphocyte phenotypes on the tumor depends mostly on the type of tumor together with its severity status and whether the cancer is a chronic inflammatory disease, which may explain the contradictory statements. In the case of CRC, which is associated with chronic inflammation, an anti-inflammatory response might be more beneficial, at least in the early stages of the disease, which may explain why resveratrol is seen to be an effective treatment for CRC cancer in vitro and in vivo [ 36 , 79 ], and thus, partly due to the ability of the resveratrol/Sirt1 axis to change from a pro-inflammatory T-lymphocyte response to an anti-inflammatory effect in the multicellular-TME.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several lines of evidence have shown that the influence of T-lymphocyte phenotypes on the tumor depends mostly on the type of tumor together with its severity status and whether the cancer is a chronic inflammatory disease, which may explain the contradictory statements. In the case of CRC, which is associated with chronic inflammation, an anti-inflammatory response might be more beneficial, at least in the early stages of the disease, which may explain why resveratrol is seen to be an effective treatment for CRC cancer in vitro and in vivo [ 36 , 79 ], and thus, partly due to the ability of the resveratrol/Sirt1 axis to change from a pro-inflammatory T-lymphocyte response to an anti-inflammatory effect in the multicellular-TME.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in a different approach, investigators used resveratrol to activate the sirtuin 1 deacetylase. The investigators found that this activation of sirtuin 1 inactivates HDACs ( Section 3.3 ) and enhances the butyrate-mediated HDACi/HMBG1 necrosis of colorectal cancer in mice [ 184 ].…”
Section: Implications For Periodontal and Intestinal Diseases: Therapy Prevention And Links To Other Diseasesmentioning
confidence: 99%
“…136 Expression of many pro-inflammatory mediators like tumor necrosis factor-a and NOS2, and anti-inflammatory mediator IL-10 are tightly controlled by deposition of activating histone modification H3K9ac and its erasure by histone deacetylase in many tissues, including the gastrointestinal track. [182][183][184] In mouse models of microbial dysbiosis and related colitis, histone deacetylase inhibition caused induction of antiinflammatory Tregs along with suppression of proinflammatory Th1 and Th17 cells. 183,184 These reports highlight the molecular and cellular impact of microbiome modulation and the underlying involvement of epigenetic changes.…”
Section: Control Of Epithelial and Immune Cells By Microbiomementioning
confidence: 99%